Aerospace series. Bonding straps for aircraft. Bonding strap assemblies with flat braided conductor copper, tin plated - 65°C up to 150°C and copper, nickel plated - 65°C up to 260°C. Product standard Part 003, (31st May 2014) - British Standards Institution,
No abstract available